DETERMINATION OF HEAVY METALS AND LEAD-STRONTIUM ISOTOPE CHARACTERIZATION FROM MERLOT SOIL SAMPLES, DEALU BUJORULUI VINEYARD - BORA, Florin Dumitru; DONICI, Alina; CĂLUGĂR, Anamaria; PETRESCU MAG, Ioan-Valentin; GÁL, Emese; BUNEA, Claudiu Ioan (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Contamination of vineyard soils with heavy-metals has been a worldwide concern, determination of these elements being important for the wine industry. The aim of this research was to determine the concentration of different heavy metals (Cd, Pb, U, Hg, As, Sr, Co, Cu, Ni and Cr) from vineyard soil on different depths in an area of vineyard cultivation from Dealu Bujorului Galati County. In order to highlight the combination of different sources, natural or anthropogenic of heavy metals the isotopic ratios for 206Pb/207Pb, 208Pb/206Pb, 206Pb/207Pb and 87Sr/86Sr from soil were established. The highest concentrations for heavy metals were recorded on the surface, with increasing depth of the soil these concentrations decrease. Regarding of Pb sources (lithogenic or anthropogenic), the average 206Pb/207Pb, 208Pb/206Pb and 206Pb/204Pb ratios in soil profile increase horizons followed the order: 1.13526 (0-10 cm 206Pb/207Pb) > 1.13427 (10-20 cm 206Pb/207Pb); 2.12626 (10-20 cm 208Pb/206Pb) > 2.12472 (10-20 cm 208Pb/206Pb) and 17.36201 (10-20 cm 206Pb/204Pb) > 17.36128 (0-10 cm 206Pb/204Pb). Statistically, in the case of 206Pb/207Pb and 208Pb/206Pb there are very significant differences between the analyzed variants while 206Pb/204Pb does not show any differences in terms of distribution on the depth of the soil profile. Our results confirm that the 207Pb/206Pb, 208Pb/206Pb, 204Pb/206Pb and 87Sr/86Sr isotope ratio can be used to track the geographical origin of wine, discriminate between wine production regions, and be used to characterize wine terroirs for forensic purpose.